PEMBERDAYAAN IBU RUMAH TANGGA KELURAHAN BUKIT DURI MELALUI METODE KAKEIBO UNTUK KETAHANAN RISIKO FINANSIAL KELUARGA: PEMBERDAYAAN IBU RUMAH TANGGA KELURAHAN BUKIT DURI MELALUI METODE KAKEIBO UNTUK KETAHANAN RISIKO FINANSIAL KELUARGA - Azizah Mursyidah; Bayu Purnama Putra; M. Apep Mustofa; Abrori; Zompi; Nugroho Adi Putro (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2026)
Effective household financial management is a key factor in achieving family welfare. Low levels of financial literacy among housewives can lead to family economic instability, consumptive behavior, and an inability to deal with unexpected financial risks. This community service program aims to improve the financial risk management capabilities of housewives in Bukit Duri, South Jakarta, through training in the Kakeibo method—a traditional Japanese financial recording and management technique. The implementation methods included interactive lectures, practical demonstrations of Kakeibo budgeting, and continuous mentoring. This activity involved 50 participants from the Family Welfare Empowerment (PKK) group. Evaluation results from pre-tests and post-tests showed a significant improvement in the understanding and practice of family financial management, with an average score increase of 35%. Participants demonstrated high enthusiasm and the ability to independently prepare monthly budgets using the Kakeibo method. This program contributes positively to women's economic empowerment and strengthens family financial resilience in urban Jakarta.